The furnishing and decoration of a dining room - Wolf, Nelle (My University, 1908)
Introduction: “More than any other spot in the home should the dining room express comfort, hospitality, and good cheer.” Since it is the one place where each day the average husband and father is permitted to enjoy the company of family, it should by all means suggest shelter, warmth, and snugness.
Citation: Wolf, Nelle. The furnishing and decoration of a dining room. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Domestic Science; Home Economics; Dining Rooms; Design; Graduating theses; Senior theses; Theses